High-ductility high-strength high-conductivity ultrafine electronic wire of 8030 aluminum alloy with high Fe content and preparation method thereof
Patent Information
- Application Number
- CN202611205897.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0009]因此,本发明提供一种高Fe含量8030铝合金高强韧高导超细电子线及其制备方法,以解决现有技术中8030超细电子线强度与导电率难以兼顾的问题,从而制备出兼顾抗拉强度、延伸率与导电率的高Fe含量8030铝合金高强韧高导超细电子线
[0034]1.本发明通过拉拔处理得到线径≤0.3mm的8030铝合金线材,然后通过低于再结晶温度且长时间的退火处理,消除8030铝合金线材中的应力和缺陷的,并保留拉拔处理形成的细长晶粒结构,得到兼顾强度、塑性和导电率的高Fe含量8030铝合金高强韧高导超细电子线;
Smart Images

Figure CN122968066A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum alloy conductor technology, specifically relating to a high-strength, high-toughness, high-conductivity ultrafine electronic wire made of high-Fe-content 8030 aluminum alloy and its preparation method. Background Technology
[0002] With the rapid development of automotive electrification and intelligence, the demand for automotive electronic wiring harnesses, as a crucial connecting component of the vehicle's electrical system, is experiencing rapid growth. Taking new energy vehicles as an example, electronic wiring harnesses account for approximately 5% of the total vehicle weight, and this proportion will further increase with the development of new energy vehicles. Electronic wiring harnesses are mainly composed of ultra-fine metallic electronic wires used to transmit electrical energy and signals. Currently, the materials for ultra-fine metallic electronic wires are mainly copper and copper alloys, but with the increasing scarcity of copper resources and the continuous rise in prices, continuing to use copper electronic wires will significantly increase the cost of automobile production.
[0003] Aluminum and aluminum alloys are commonly used as conductor materials due to their excellent electrical conductivity, and they have mature applications in the power transmission line industry. Aluminum's density is about one-third that of copper, and its price is about one-quarter that of copper. Using aluminum alloy electronic wires can reduce the overall weight of new energy vehicles, increase their driving range, and significantly reduce production costs. 8030 aluminum alloy is maturely used in the cable conductor field. According to the GB / T 3190-2020 standard, the mass fraction of Fe in 8030 aluminum alloy is 0.30%–0.80%, and the mass fraction of Cu is 0.15%–0.30%. 8030 aluminum alloy cables, while providing the same electrical performance, weigh only 45%–50% of copper cables. The advantages of aluminum alloy electronic wires are highly compatible with the development trend of lightweighting and cost reduction in new energy vehicles; therefore, the development of aluminum alloy electronic wires is an inevitable trend.
[0004] However, research on aluminum conductor materials in China started relatively late, and the fabrication technology for aluminum alloy electronic wires is still immature. For electronic wires used in new energy vehicles, the relationship between strength and conductivity is the main bottleneck limiting the application of aluminum alloy wires.
[0005] Improving the strength of aluminum alloy conductors typically relies on methods such as solid solution strengthening and deformation strengthening. However, these methods increase electron scattering, leading to a decrease in conductivity. In existing technologies, the commonly used annealing treatment can promote the precipitation of solid solution elements in the matrix, eliminate residual stress introduced by processing, thereby reducing the degree of matrix lattice distortion, weakening electron scattering, and improving conductivity.
[0006] In actual production, to ensure processing and forming performance, a lower Fe content (usually below 0.5%) is typically chosen within the standard composition range of 8030 aluminum alloy. However, the strengthening of 8030 aluminum alloy mainly relies on the precipitation strengthening effect of Fe-rich second phase. Low Fe content directly leads to insufficient number of strengthening phases, making it difficult for the alloy to meet the required strength. At the same time, low Fe alloys have a lower recrystallization temperature and are prone to recrystallization during service, further weakening the strength. This makes it difficult for the alloy to simultaneously meet the stringent requirements of automotive electronic wires for both strength and conductivity. Therefore, increasing the Fe content is considered an important direction to overcome the above bottlenecks, because a high Fe content can not only effectively improve strength by increasing the number of second phases, but also increase the recrystallization temperature. However, as the Fe content increases, the number of second phase particles increases and their distribution becomes more complex. Conventional annealing processes become increasingly difficult to balance conductivity, strength, and machinability, often resulting in trade-offs and even a decline in overall performance.
[0007] Currently, there is no mature dedicated annealing technology for 8030 alloy (or Al-Fe alloy). The main alloying element, Fe, has extremely low solid solubility in the Al matrix of 8030 aluminum alloy, and no dissolved elements precipitate as a second phase during annealing. This significantly reduces the effectiveness of commonly used annealing processes on 8030 aluminum alloy; although residual stress can be eliminated, it often comes at the cost of a substantial decrease in strength.
[0008] Therefore, there is an urgent need to develop a method for preparing high-strength, high-toughness, and high-conductivity ultrafine electronic wires suitable for high-Fe-content 8030 aluminum alloy, in order to solve the current technical problem of balancing strength and conductivity in 8030 ultrafine electronic wires. Summary of the Invention
[0009] Therefore, this invention provides a high-strength, high-toughness, and high-conductivity ultrafine electronic wire of 8030 aluminum alloy with high Fe content and its preparation method, so as to solve the problem that it is difficult to balance the strength and conductivity of 8030 ultrafine electronic wire in the prior art, thereby preparing a high-strength, high-toughness, and high-conductivity ultrafine electronic wire of 8030 aluminum alloy with high Fe content that balances tensile strength, elongation and conductivity.
[0010] To address one of the aforementioned problems, this invention provides a method for preparing high-strength, high-toughness, and high-conductivity ultrafine electronic wires from high-Fe-content 8030 aluminum alloy, comprising the following steps:
[0011] Step 1): The 8030 aluminum alloy rod is drawn to obtain 8030 aluminum alloy wire, wherein the diameter of the 8030 aluminum alloy wire is ≤0.3mm;
[0012] Step 2): Anneal the 8030 aluminum alloy wire to obtain a high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire;
[0013] The annealing treatment ensures that the average aspect ratio of the high-Fe content 8030 aluminum alloy high-strength, high-toughness, and high-conductivity ultrafine electronic wires is ≥5 and the geometrically necessary dislocation density is less than 7.5 × 10⁻⁶. 14 / m², the grains of the high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire are slender along the wire axis;
[0014] The annealing process is performed at a temperature of T1 and a time of t1, wherein 150℃≤T1≤190℃ and 24h≤t1≤240h.
[0015] In some embodiments, the annealing process is performed in a box-type resistance furnace, specifically including:
[0016] After the internal temperature of the box-type resistance furnace rises to T1, the 8030 aluminum alloy wire is placed in the furnace for annealing. After annealing, the 8030 aluminum alloy wire is taken out and air-cooled to room temperature.
[0017] In some embodiments, the high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire has a tensile strength ≥120MPa, an elongation ≥12%, and a conductivity ≥62%IACS.
[0018] In some embodiments, the high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire comprises, by weight percentage: iron: 0.6~0.8wt%, copper: 0.15~0.3wt%, silicon <0.1wt%, magnesium <0.05wt%, zinc <0.05wt%, boron: 0.001~0.04wt%, the sum of impurity element contents ≤0.1wt%, and the balance being aluminum.
[0019] In some embodiments, the method for preparing the 8030 aluminum alloy wire includes the following steps:
[0020] Step 1.1): Perform a drawing process on the 8030 aluminum alloy rod to obtain the drawn 8030 alloy wire;
[0021] Step 1.2): The drawn 8030 alloy wire is subjected to intermediate annealing to obtain annealed 8030 alloy wire;
[0022] Step 1.3): The annealed 8030 alloy wire is subjected to a secondary drawing process to obtain the 8030 aluminum alloy wire.
[0023] In some embodiments, the method for preparing the 8030 aluminum alloy rod includes:
[0024] The 8030 aluminum alloy billet rod is prepared by continuous casting and rolling process; or...
[0025] After homogenization annealing of 8030 aluminum alloy ingots, the 8030 aluminum alloy rods are obtained by hot extrusion.
[0026] In some embodiments, the homogenization annealing treatment is performed at a temperature of T2 and for a time of t2.
[0027] Among them, 500℃≤T2≤540℃, 12h≤t2≤24h.
[0028] In some embodiments, the intermediate annealing treatment is performed at a temperature of T3 and for a time of t3.
[0029] Among them, 260℃≤T3≤360℃, 30min≤t3≤90min.
[0030] In some embodiments, the primary drawing process is cold drawing, with 17 to 22 drawing passes, and the deformation amount per pass should be between 10% and 20%, with a wire exit speed of 40 to 100 m / min.
[0031] In some embodiments, the secondary drawing process is cold drawing, with 20 to 25 drawing passes, and the deformation amount per pass should be between 5% and 10%, with a wire exit speed of 100 to 500 m / min.
[0032] On the other hand, the present invention provides a high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire, which is prepared by the above-mentioned preparation method. The wire diameter of the high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire is ≤0.3mm, its grains are slender along the axial direction, the average grain length-to-diameter ratio is ≥5, the tensile strength is ≥120MPa, the elongation is ≥12%, and the conductivity is ≥62%IACS.
[0033] The high-strength, high-toughness, and high-conductivity ultrafine electronic wire of high-Fe-content 8030 aluminum alloy and its preparation method provided by the present invention have the following beneficial effects:
[0034] 1. This invention obtains 8030 aluminum alloy wire with a diameter ≤0.3mm through drawing process, and then eliminates stress and defects in the 8030 aluminum alloy wire through long-term annealing treatment below recrystallization temperature, while retaining the slender grain structure formed by the drawing process, thus obtaining high-strength, high-toughness, high-conductivity ultrafine electronic wire of high Fe content 8030 aluminum alloy that takes into account strength, plasticity and conductivity.
[0035] The 8030 aluminum alloy wire obtained by the drawing process of this invention has a diameter ≤0.3mm. During the intense drawing process necessary for ultra-fine wires, the metal grains are elongated into submicron and even nanoscale fibrous structures, with the density of grain boundaries and fiber boundaries increasing by orders of magnitude. According to Matthiessen's rule, the conductivity of conventional wire diameter conductors is mainly limited by the scattering of solid solution impurity atoms. However, in the high-strength, high-toughness, and high-conductivity ultra-fine electronic wire of the high-Fe content 8030 aluminum alloy of this invention, grain boundary scattering and dislocation scattering are significantly enhanced and have replaced impurity scattering as the main limiting factor for conductivity. This indicates that the conductivity control mechanism of this ultra-fine wire has shifted from "solid solution atom scattering dominance" to "interface scattering (grain boundaries, fiber boundaries) and dislocation scattering dominance." Even with recrystallization annealing to induce full precipitation of the second phase, the conductivity remains difficult to substantially improve due to the persistent presence of high-density interfaces and their continued strong scattering of electrons. Conversely, high-temperature conditions easily induce complete recrystallization and abnormal grain growth, irreversibly destroying the fibrous structure, high-density grain boundaries, and favorable microstructures that maintain the high strength and high conductivity of the ultrafine wires. <111> Texture. Based on the above mechanism, this invention employs a low-temperature, long-time annealing process on drawn 8030 aluminum alloy wires. This effectively eliminates residual stress and crystal defects while preserving the fine grain structure and grain boundaries to the greatest extent, thereby achieving a synergistic improvement in tensile strength and conductivity. Furthermore, the average aspect ratio and geometrically necessary dislocation density of the high-strength, high-toughness, and high-conductivity ultrafine electronic wires of high-Fe-content 8030 aluminum alloy are used as indicators to control the parameters of the annealing process, thus enabling the annealing process to effectively preserve the fine grain structure while eliminating residual stress. Attached Figure Description
[0036] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.
[0037] Figure 1 This is a flowchart of a method for preparing high-strength, high-toughness, and high-conductivity ultrafine electronic wires from high-Fe-content 8030 aluminum alloy, provided by the present invention.
[0038] Figure 2 The electron backscattering diffraction (EBSD) pattern of the high-strength, high-toughness, high-conductivity ultrafine electron wire of high-Fe-content 8030 aluminum alloy with a diameter of 0.26 mm in Example 1;
[0039] Figure 3 The KAM distribution diagram of the high-strength, high-toughness, high-conductivity ultrafine electronic wire of high-Fe-content 8030 aluminum alloy with a diameter of 0.26 mm in Example 1 is shown.
[0040] Figure 4 The KAM distribution diagram of 1.2 mm diameter 8030 alloy wire without intermediate annealing in Comparative Example 1 is shown.
[0041] Figure 5 The KAM distribution diagram of the 1.2mm diameter 8030 alloy wire after intermediate annealing in Comparative Example 2 is shown.
[0042] Figure 6 The KAM distribution diagram of the 0.26mm diameter 8030 alloy wire in Comparative Example 3 that has not undergone step 6) annealing is shown.
[0043] Figure 7 The electron backscattering diffraction (EBSD) pattern of the high-strength, high-toughness, high-conductivity ultrafine electron wire of high-Fe-content 8030 aluminum alloy with a diameter of 0.26 mm in Comparative Example 4 is shown.
[0044] Figure 8 The electron backscattering diffraction (EBSD) pattern of the high-strength, high-toughness, high-conductivity ultrafine electron wire of high-Fe-content 8030 aluminum alloy with a diameter of 0.26 mm in Comparative Example 8 is shown. Detailed Implementation
[0045] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific embodiments, structures, features, and effects according to the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. In the following description, different "an embodiment" or "an embodiment" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.
[0046] See also Figures 1 to 8 As shown in the embodiments of the present invention, the present invention provides a method for preparing high-strength, high-toughness, and high-conductivity ultrafine electronic wires from high-Fe-content 8030 aluminum alloy, such as... Figure 1 As shown, it includes the following steps:
[0047] Step 1): The 8030 aluminum alloy rod is drawn to obtain 8030 aluminum alloy wire, wherein the diameter of the 8030 aluminum alloy wire is ≤0.3mm;
[0048] Step 2): Anneal the 8030 aluminum alloy wire to obtain a high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire;
[0049] The annealing treatment ensures that the average aspect ratio of the high-Fe content 8030 aluminum alloy high-strength, high-toughness, and high-conductivity ultrafine electronic wires is ≥5 and the geometrically necessary dislocation density is less than 7.5 × 10⁻⁶. 14 / m², the grains of the high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire are slender along the wire axis;
[0050] The average grain aspect ratio and geometrically necessary dislocation density were obtained by processing the acquired EBSD data.
[0051] The annealing process is performed at a temperature of T1 and a time of t1, wherein 150℃≤T1≤190℃ and 24h≤t1≤240h.
[0052] In some embodiments, the annealing process is performed in a box-type resistance furnace, specifically including:
[0053] After the internal temperature of the box-type resistance furnace rises to T1, the 8030 aluminum alloy wire is placed in the furnace for annealing. After annealing, the 8030 aluminum alloy wire is taken out and air-cooled to room temperature.
[0054] In some embodiments, the high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire has a tensile strength ≥120MPa, an elongation ≥12%, and a conductivity ≥62%IACS.
[0055] In some embodiments, the high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire comprises, by weight percentage: iron: 0.6~0.8wt%, copper: 0.15~0.3wt%, silicon <0.1wt%, magnesium <0.05wt%, zinc <0.05wt%, boron: 0.001~0.04wt%, the sum of impurity element contents ≤0.1wt%, and the balance being aluminum.
[0056] Existing techniques typically select a lower Fe content within the standard composition range of 8030 alloy to ensure good machinability. This invention improves the strength and heat resistance of the electron wire by increasing the Fe content within the standard composition range of 8030 alloy.
[0057] In some embodiments, the method for preparing the 8030 aluminum alloy wire includes the following steps:
[0058] Step 1.1): Perform a drawing process on the 8030 aluminum alloy rod to obtain the drawn 8030 alloy wire;
[0059] Step 1.2): The drawn 8030 alloy wire is subjected to intermediate annealing to obtain annealed 8030 alloy wire;
[0060] Step 1.3): The annealed 8030 alloy wire is subjected to a secondary drawing process to obtain the 8030 aluminum alloy wire.
[0061] During a single drawing process, as the amount of drawing deformation increases, the work hardening effect of the 8030 aluminum alloy rod intensifies, leading to a continuous increase in strength but a sharp decrease in plasticity. This makes it difficult to directly produce 8030 aluminum alloy wire through a single drawing pass. Therefore, this invention incorporates an intermediate annealing treatment between the two drawing processes to eliminate residual stress accumulated during the first drawing process and to promote recrystallization within the 8030 aluminum alloy rod, restoring its plastic deformation capacity and thus meeting the process requirements of a second drawing process.
[0062] In some embodiments, the method for preparing the 8030 aluminum alloy rod includes:
[0063] The 8030 aluminum alloy billet rod is prepared by continuous casting and rolling process; or...
[0064] After homogenization annealing of 8030 aluminum alloy ingots, the 8030 aluminum alloy rods are obtained by hot extrusion.
[0065] In some embodiments, the homogenization annealing treatment is performed at a temperature of T2 and for a time of t2.
[0066] Among them, 500℃≤T2≤540℃, 12h≤t2≤24h.
[0067] In some embodiments, the intermediate annealing treatment is performed at a temperature of T3 and for a time of t3.
[0068] Among them, 260℃≤T3≤360℃, 30min≤t3≤90min.
[0069] In some embodiments, the primary drawing process is cold drawing, with 17 to 22 drawing passes, and the deformation amount per pass should be between 10% and 20%, with a wire exit speed of 40 to 100 m / min.
[0070] In some embodiments, the secondary drawing process is cold drawing, with 20 to 25 drawing passes, and the deformation amount per pass should be between 5% and 10%, with a wire exit speed of 100 to 500 m / min.
[0071] On the other hand, the present invention provides a high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire, which is prepared by the above-mentioned preparation method. The wire diameter of the high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire is ≤0.3mm, its grains are slender along the axial direction, the average grain length-to-diameter ratio is ≥5, the tensile strength is ≥120MPa, the elongation is ≥12%, and the conductivity is ≥62%IACS.
[0072] The present invention will be further described below with reference to specific embodiments and comparative examples.
[0073] Example 1:
[0074] This embodiment provides a method for preparing high-strength, high-toughness, and high-conductivity ultrafine electronic wires from high-Fe-content 8030 aluminum alloy, including the following steps:
[0075] Step 1): Place the raw material in a melting furnace and heat it until it is completely melted. Stir the melt thoroughly and keep it warm. Then pour the melt into a mold and obtain an 8030 aluminum alloy ingot after cooling and solidification.
[0076] The 8030 aluminum alloy ingot, by weight percentage, contains the following elements: iron: 0.75wt%, copper: 0.24wt%, silicon <0.1wt%, magnesium <0.05wt%, zinc <0.05wt%, boron: 0.001~0.04wt%, the sum of impurity elements ≤0.1wt%, and the balance is aluminum;
[0077] Step 2): The 8030 aluminum alloy ingot is subjected to homogenization annealing at 540℃ and held for 24 hours; then, the 8030 aluminum alloy ingot is extruded into shape using a horizontal extrusion press at an extrusion temperature of 400℃ to obtain 8030 aluminum alloy rods with a diameter of 9.5mm.
[0078] Step 3): The 8030 aluminum alloy rod with a diameter of 9.5mm is cold drawn. After 18 drawing passes, an 8030 alloy wire with a diameter of 1.2mm is obtained. The wire drawing speed is 40m / min.
[0079] Step 4): Perform intermediate annealing on 8030 alloy wire with a diameter of 1.2 mm. The annealing temperature is 300℃ and the holding time is 60 min. Then air cool to room temperature to obtain 8030 alloy wire after intermediate annealing.
[0080] Step 5): The 8030 alloy wire with a diameter of 1.2 mm after intermediate annealing is cold drawn. After 20 drawing passes, an 8030 alloy wire with a diameter of 0.26 mm is obtained. The wire drawing speed is 500 m / min.
[0081] Step 6): After the internal temperature of the box-type resistance furnace rises to 170℃, put the 8030 alloy wire with a diameter of 0.26mm into the box-type resistance furnace for annealing treatment. The holding time is 48h. After annealing, take out the 8030 aluminum alloy wire and air cool it to room temperature to obtain high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire.
[0082] The high-strength, high-toughness, and high-conductivity ultrafine electron wire with a diameter of 0.26 mm from high-Fe-content 8030 aluminum alloy obtained in Example 1 was characterized using EBSD technology. The resulting electron backscatter diffraction (EBSD) pattern is shown below. Figure 2 As shown in the diagram, the horizontal direction represents the pulling direction. (From...) Figure 2As can be seen, after the annealing process of this invention, some grains recrystallized, but the overall slender grain structure distributed along the drawing direction was retained. The average grain aspect ratio was measured to be 5.18 according to EBSD results. The high-strength, high-toughness, and high-conductivity ultrafine electron wires of the high-Fe content 8030 aluminum alloy obtained in Example 1 were characterized using KAM technology. The resulting KAM distribution diagram is shown below. Figure 3 As shown, the geometrically necessary dislocation density calculated based on the KAM results is 5.17 × 10⁻⁶. 14 / m². The above microstructural features, combined with the data in Table 1, indicate that the retention of the slender grain structure after annealing allows the high-Fe-content 8030 aluminum alloy to possess both high strength, high toughness, and high conductivity ultrafine electronic wires with good tensile strength and electrical conductivity.
[0083] Example 2:
[0084] The difference between Example 2 and Example 1 is that the Fe content was adjusted to 0.65 wt% and the copper content to 0.3 wt%.
[0085] In step 6), the annealing temperature is 150℃ and the holding time is 220h.
[0086] Example 3:
[0087] The difference between Example 3 and Example 1 is that the Fe content was adjusted to 0.8 wt%.
[0088] In step 6), the annealing temperature is 190℃ and the holding time is 24h.
[0089] Comparative Example 1:
[0090] The difference between Comparative Example 1 and Example 1 is that steps 4) and 6 were not performed.
[0091] When cold drawing 1.2mm diameter 8030 alloy wire without intermediate annealing, wire breakage frequently occurs during the drawing process, making it impossible to complete the cold drawing process.
[0092] The KAM (Kinetic Aluminum Acrylonitrile) pattern was used to characterize the 1.2 mm diameter 8030 alloy wire obtained in this comparative example, which had not undergone intermediate annealing. The resulting KAM pattern is shown in the figure below. Figure 4 As shown in the figure (blue areas represent areas with lower residual stress, and green areas represent areas with higher residual stress), a large amount of residual stress is distributed along the drawing direction (transverse direction). This residual stress leads to a significant reduction in the plasticity of the 1.2mm diameter 8030 alloy wire that has not undergone intermediate annealing, resulting in a loss of its ability to continue deforming and thus failing to meet the requirements of cold drawing.
[0093] Comparative Example 2:
[0094] The difference between Comparative Example 2 and Example 1 is that steps 5) and 6 were not performed.
[0095] The KAM (Kinetic Atomography) technique was used to characterize 1.2 mm diameter intermediate-annealed 8030 alloy wire. The resulting KAM distribution diagram is shown below. Figure 5 As shown in the diagram (blue areas represent areas with lower residual stress, and green areas represent areas with higher residual stress). From Figure 5 As can be seen from the data in Table 1, the intermediate annealing treatment eliminates the stress introduced into the wire during drawing, allowing the wire to regain its plasticity and be ready for a second drawing.
[0096] Comparative Example 3:
[0097] The difference between Comparative Example 3 and Example 1 is that step 6 was not performed.
[0098] The 8030 alloy wire with a diameter of 0.26 mm obtained in Comparative Example 3 was characterized using KAM technology. The resulting KAM distribution diagram is shown below. Figure 6 As shown, the geometrically necessary dislocation density calculated based on the KAM results is 17.01 × 10⁻⁶. 14 / m², and Figure 3 (KAM distribution diagram of the ultrafine electron wires obtained in Example 1) A comparison shows that... Figure 6 The residual strain and dislocation density of the wire shown are significantly higher than those of the wire shown. Figure 3 The ultrafine electronic wire shown indicates that the wire in Comparative Example 3, which was not annealed in step 6), has a significant amount of residual drawing defects. In contrast, the wire in Example 1, after annealing in step 6), exhibits a significant reduction in residual strain and dislocation density, demonstrating that the annealing process in step 6) effectively eliminates crystal defects introduced by the drawing process. Based on the EBSD results, the average grain aspect ratio is calculated to be 12.69, indicating that the drawing process imparts a slender grain structure extending along the drawing direction to the wire.
[0099] Comparative Example 4:
[0100] The difference between Comparative Example 4 and Example 1 is that the annealing temperature in step 6) is 160°C and the holding time is 300h.
[0101] The high-strength, high-toughness, and high-conductivity ultrafine electron wire with a diameter of 0.26 mm from high-Fe-content 8030 aluminum alloy, obtained in Comparative Example 4, was characterized using EBSD technology. The resulting electron backscatter diffraction (EBSD) pattern is shown below. Figure 7 As shown in the diagram, the horizontal direction represents the pulling direction. (From...) Figure 7 It is evident that even at relatively low annealing temperatures, excessively high annealing times can still lead to grain structure regression, with significant degradation of the elongated grain structure and an average grain aspect ratio decreasing to 2.36. Based on KAM results, the geometrically necessary dislocation density is calculated to be 5.61 × 10⁻⁶. 14 / m² indicates that although the dislocations and residual stresses introduced by drawing were effectively eliminated, the disappearance of the elongated grain structure resulted in an increase in conductivity compared to before annealing, but it was still lower than the conductivity when the elongated grain structure was retained in Example 1, and the tensile strength had decreased significantly.
[0102] Comparative Example 5:
[0103] The difference between Comparative Example 5 and Example 1 is that the annealing temperature in step 6) is 190°C and the holding time is 12h.
[0104] Comparative Example 6:
[0105] The difference between Comparative Example 6 and Example 1 is that the annealing temperature in step 6) is 300°C and the holding time is 48h.
[0106] Comparative Example 7:
[0107] The difference between Comparative Example 7 and Example 1 is that the annealing temperature in step 6) is 120°C and the holding time is 96h.
[0108] Comparative Example 8:
[0109] The difference between Comparative Example 8 and Example 1 is that the annealing temperature in step 6) is 300°C and the holding time is 6 hours.
[0110] The high-strength, high-toughness, and high-conductivity ultrafine electron wire with a diameter of 0.26 mm from high-Fe-content 8030 aluminum alloy, obtained in Comparative Example 8, was characterized using EBSD technology. The resulting electron backscatter diffraction (EBSD) pattern is shown below. Figure 8 As shown in the diagram, the horizontal direction represents the pulling direction. (From...) Figure 8 It is evident that even with an extremely short annealing time, excessively high annealing temperatures can still lead to rapid and complete recrystallization of the wire, resulting in the complete disappearance of the elongated grain structure and a decrease in the average grain aspect ratio to 1.67. Based on KAM results, the geometrically necessary dislocation density is calculated to be 4.07 × 10⁻⁶. 14 / m² indicates that recrystallization effectively eliminates the dislocations and residual stresses introduced by drawing; however, the disappearance of the elongated grain structure leads to an increase in conductivity compared to before annealing, but the increase is limited and still lower than the conductivity when the elongated grain structure was retained in Example 1, while the tensile strength has decreased significantly.
[0111] The tensile strength, conductivity, and elongation of the 8030 alloy wires or high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wires prepared in the above embodiments and comparative examples were tested, and the specific results are shown in Table 1.
[0112]
[0113] As shown in Table 1, the high-Fe content 8030 aluminum alloy high-strength, high-toughness, and high-conductivity ultrafine electronic wires of Examples 1 to 3 prepared by the method provided by this invention all possess good tensile strength and conductivity. The KAM and EBSD characterization results of the examples and comparative examples show that only when the high-Fe content 8030 aluminum alloy high-strength, high-toughness, and high-conductivity ultrafine electronic wires after annealing simultaneously satisfy the following conditions: average grain aspect ratio ≥ 5 and geometrically necessary dislocation density < 7.5 × 10⁻⁶ 14 Only when the elongation is within a certain range (e.g., / m²) can it possess good tensile strength, electrical conductivity, and elongation.
[0114] Comparing Comparative Example 1 and Comparative Example 2, it can be seen that the elongation of the 1.2mm diameter 8030 alloy wire after one drawing is only 1.4%, which cannot meet the plasticity requirements of subsequent drawing processes. Therefore, intermediate annealing is required between drawing processes to eliminate processing stress and improve wire plasticity. The results of Comparative Example 3 show that although the high-strength, high-toughness, and high-conductivity ultrafine electronic wire of high-Fe content 8030 aluminum alloy achieves the highest strength after two drawing processes, its conductivity and elongation are the lowest. Therefore, final annealing is needed to improve both.
[0115] The results of Comparative Examples 4 and 5 show that low-temperature, long-time annealing is a key control factor in the annealing process: too short an annealing time is detrimental to the effective recovery of conductivity of the ultrafine electronic wires, while too long an annealing time will result in tensile strength lower than the service requirements. The results of Comparative Examples 6 to 8 further illustrate that too low an annealing temperature cannot effectively eliminate residual stress, while too high a temperature will cause a rapid decrease in tensile strength. Even if the annealing time is shortened, it is difficult to simultaneously meet the service requirements for both tensile strength and conductivity.
[0116] In summary, the preparation method proposed in this invention effectively eliminates the processing stress introduced by the first drawing through intermediate annealing, ensuring the smooth progress of subsequent drawing processes; and significantly improves conductivity through low-temperature long-term final annealing treatment, thereby successfully preparing 8030 alloy ultrafine wire with both high strength and high conductivity.
[0117] It will be readily understood by those skilled in the art that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.
[0118] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the protection scope of the present invention.
Claims
1. A method for preparing high-strength, high-toughness, and high-conductivity ultrafine electronic wires from high-Fe-content 8030 aluminum alloy, characterized in that, Includes the following steps: Step 1): The 8030 aluminum alloy rod is drawn to obtain 8030 aluminum alloy wire, wherein the diameter of the 8030 aluminum alloy wire is ≤0.3mm; Step 2): Anneal the 8030 aluminum alloy wire to obtain a high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire; The annealing treatment ensures that the average aspect ratio of the high-Fe content 8030 aluminum alloy high-strength, high-toughness, and high-conductivity ultrafine electronic wires is ≥5 and the geometrically necessary dislocation density is less than 7.5 × 10⁻⁶. 14 / m 2 The high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire has slender grains along the wire axis. The annealing process is performed at a temperature of T1 and a time of t1, wherein 150℃≤T1≤190℃ and 24h≤t1≤240h.
2. The preparation method according to claim 1, characterized in that, The annealing process is carried out in a box-type resistance furnace, specifically including: After the internal temperature of the box-type resistance furnace rises to T1, the 8030 aluminum alloy wire is placed in the furnace for annealing. After annealing, the 8030 aluminum alloy wire is taken out and air-cooled to room temperature.
3. The preparation method according to claim 1, characterized in that, The high-Fe-content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire has a tensile strength ≥120MPa, an elongation ≥12%, and a conductivity ≥62%IACS.
4. The preparation method according to claim 1, characterized in that, The high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire has the following elemental composition by weight percentage: iron: 0.6~0.8wt%, copper: 0.15~0.3wt%, silicon <0.1wt%, magnesium <0.05wt%, zinc <0.05wt%, boron: 0.001~0.04wt%, the sum of impurity element content ≤0.1wt%, and the balance being aluminum.
5. The preparation method according to claim 1, characterized in that, The preparation method of the 8030 aluminum alloy wire includes the following steps: Step 1.1): Perform a drawing process on the 8030 aluminum alloy rod to obtain the drawn 8030 alloy wire; Step 1.2): The drawn 8030 alloy wire is subjected to intermediate annealing to obtain annealed 8030 alloy wire; Step 1.3): The annealed 8030 alloy wire is subjected to a secondary drawing process to obtain the 8030 aluminum alloy wire.
6. The preparation method according to claim 5, characterized in that, The preparation method of the 8030 aluminum alloy rod includes: The 8030 aluminum alloy billet rod is prepared by continuous casting and rolling process; or... After homogenization annealing of 8030 aluminum alloy ingots, the 8030 aluminum alloy rods are obtained by hot extrusion.
7. The preparation method according to claim 6, characterized in that, The homogenization annealing process is performed at a temperature of T2 and a time of t2. Among them, 500℃≤T2≤540℃, 12h≤t2≤24h.
8. The preparation method according to claim 5, characterized in that, The intermediate annealing process is performed at a temperature of T3 and a time of t3. Among them, 260℃≤T3≤360℃, 30min≤t3≤90min.
9. The preparation method according to claim 5, characterized in that, The primary drawing process is cold drawing, with 17 to 22 drawing passes, and the deformation per pass should be between 10% and 20%, with an exit speed of 40 to 100 m / min; and / or, The secondary drawing process is cold drawing, with 20 to 25 drawing passes, and the deformation in each pass should be between 5% and 10%, with a wire exit speed of 100 to 500 m / min.
10. A high-strength, high-toughness, high-conductivity ultrafine electronic wire made of high-Fe-content 8030 aluminum alloy, characterized in that, The high-Fe content 8030 aluminum alloy high-strength, high-toughness, high-conductivity ultrafine electronic wire, prepared by any one of claims 1-9, has a wire diameter ≤0.3mm, its grains are slender along the axial direction, the average grain length-to-diameter ratio is ≥5, the tensile strength is ≥120MPa, the elongation is ≥12%, and the conductivity is ≥62%IACS.